Rancang Bangun Sistem Pencahayaan Otomatis Berbasis Pemrograman Ladder PLC (Programmable Logic Controller) Zelio - Ferdiansyah, Andri; Swamardika, Ida Bagus Alit; Agung, IGA Putu Raka (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
For efficiency of electrical energy consumption and safety reason, lighting source need to be controlled when building leaved by owner . It can be solved by build a lighting system that can be controlled automatically depend the time programmed and light intensity level at room. LDR (Light Dependent Resistor) and real time clock function at zelio used as input signal to activate the lamps. Zelio PLC (Programmable Logic Controller) is used to be main controller what processed all the input signals.
Keywords: PLC,zelio,LDR,real time clock